Obliczanie Parametrów Przepływu w Rurze Uderzeniowej z Uwzględnieniem Jonizacji - Nowak, E. (Engineering Transactions, 1966)
The aim of the present paper is to determine the thermodynamic parameters of an electric shock tube. The flow is described by means of the classical shock tube. The body is described using the scheme of a multiply ionized gas introduced by A. SZANIAWSKI, Thermodynamic equilibrium is assumed in every region dissipation being disregarded. The relations between the flow parameters (temperature, density, velocity of flow, degree of ionization, pressure and velocity of sound) and the shock-wave velocity and initial density in the tube are obtained by numerical methods.